Bronchodilator reversibility test for broncho-obstructive syndrome detection and differential diagnosis of bronchial asthma and chronic obstructive pulmonary disease - Melnyk, V. P.; Panasiuk, O. V.; Sadomova-Andrianova, H. V.; Molchanova, M. S.; Scoryk, V. V. (Zaporozhye Medical Journal, 2019)
Purpose – to analyze the method of bronchodilator reversibility test (BRT) at different doses of salbutamol in patients with bronchial asthma (BA) and chronic obstructive pulmonary disease (COPD). Materials and methods. We examined 80 patients with broncho-obstructive syndrome, including 50 patients with a mild persistent BA (Group I) and 30 patients with COPD of moderate (course B) severity (Group II). All patients underwent routine methods of investigation: general clinical, laboratory, pulmonary function test, radiography of the chest organs (if needed), and statistical methods were used. Results. Two methods of BRT were performed that differed in the dose of salbutamol to examine the patients with BA and COPD. All 50 patients with BA were first examined for bronchodilator reversibility with 200 micrograms of salbutamol and then, usually in 2 weeks, with 400 micrograms of salbutamol. Reversibility was in all the patients with BA within 15 minutes after 200 micrograms of salbutamol inhalation, but in 30 patients (60 %) it was full (12 % and more than the previous, >200 ml), and in 20 patients it was partial (less than 12 % or 200 ml). Full reversibility was found in 46 out of the 50 patients (92 %) within 30 minutes and it was 12 % or more (>200 ml) in all the patients only within 45 minutes. When using a salbutamol dose of 400 mg in BRT, the following results were obtained: full reversibility was in 47 (94 %) patients within 15 minutes and in another 3 patients within 30 minutes, that is in all the patients with BA. 16 (53.3 %) patients with COPD were considered nonreversible following administration a dose of salbutamol 200 micrograms within 15 minutes and partial reversibility was in 14 (46.7 %) patients with COPD. Partial reversibility was found in 10 patients (33.3 %) after 30 minutes, and 6 patients (20.0 %) were nonreversible or reversibility was within 2–3 %; in 4 out of the 6 patients (93.24 % in total) partial reversibility was only after 45 minutes and the remaining two patients were nonreversible even after 60 minutes of the examination. BRT revealed partial reversibility at a salbutamol dose of 400 micrograms in 26 (86.6 %) patients with COPD within 15 minutes, in another 3 (96.6 %) patients – within 30 minutes and after 45 minutes – in all patients; none of the patients showed full reversibility. Conclusions. According to conducted study, salbutamol for BRT can be used at a dose of 200 and 400 mcg in patients with BA, but the time of repeated spirometry should be different: at 200 mcg – not earlier than 30 minutes, or preferably 45 minutes; and at 400 mcg – 15 minutes after or a maximum of 30 minutes. In patients with COPD, the use of salbutamol at a dose of 200 mcg is impractical, but a dose of 400 mcg should be used and repeated spirometry is needed not earlier than 30 minutes after a test dose of the drug.